HUBUNGAN PENGETAHUAN PENGAWAS MINUM OBAT (PMO) DENGAN TINGKAT KEPATUHAN MINUM OBAT PADA PASIEN TB PARU DI WILAYAH KERJA PUSKESMAS DARUL FALAH - Eva Sulistiany; Azwarni Azwarni; Nora Hayani; Elfida Elfida (Media Bina Ilmiah, 2022)
World Health Organization (WHO) report in 2015, estimated at the global level of 9.6 million cases of pulmonary TB with 3.2 million cases of whom were women. With 1.5 million deaths due to pulmonary TB, 480,000 cases are women. The prevalence of pulmonary TB is based on a doctor's diagnosis in Indonesia in 2018 as much as 0.4% where the target is in 2019 the prevalence of pulmonary TB becomes 245 / 100,000 population Study of TB Inventory (Global Report TB 2018) Incidence of TB 321 per 100,000 (Riskesdas, 2018). In order for patients to be cured they must take medication regularly as directed, spend the medicine according to the specified time (6-12 months) without interruption and involve health workers or family members to monitor and ensure TB patients adhere to taking medication. This study aims to determine the relationship between the knowledge of supervisors taking medication (PMO) and the level of medication adherence in pulmonary TB patients in the Darul Falah Community Health Center Work Area in 2019. The design of this study used an analytic type with a cross sectional design. The number of samples in this study were 31 respondents with the Total Sampling technique. The results of this study indicate that of the 31 respondents the majority obediently consumed pulmonary TB drugs as many as 29 respondents (93.5%) and the majority of PMOs had sufficient knowledge as many as 13 respondents (41.9%). The researcher also concluded that there was no relationship between the knowledge supervisors taking medication (PMO) and the level of medication adherence in pulmonary TB patients in the Darul Falah Community Health Center Working Area with a p-value of 0.106 (p> 0.05). The researcher suggested to the Darul Falah Health Center to be able to conduct socialization of policies in an effort to increase PMO knowledge in monitoring taking medication in pulmonary TB patients.